Analysis of Computer based Management Information Systems in the Decision Making Process - Utami, Batina Yulia; Sabandi, Ahmad; Irsyad, Irsyad (International Journal of Educational Dynamics, 2024)
Computer-based management information systems mean that computers play an important role. An organization's technical capabilities, or an organization's ability to adapt to internal and external conditions, are critical to organizational success.In the midst of rapid technological advances, using Management Information Systems is the best way to manage high-quality information resources. The management role requires the effective deployment and use of resources to achieve specific goals. As a result, this task will help management by providing information quickly and precisely. To support company goals, an effective management information system is needed. In reality, the term "computer-based" or "computer-based information processing" is always associated with good and efficient management information systems. Information is required for each process, which is partly created by the management information system. To meet the needs and decisions made by organizations at each level of management, data and information produced by information systems through special analysis are very helpful. Therefore, the aim of establishing a management information system (MIS) is to provide organizations with data and information that assists in making management decisions, both relating to routine and strategic management and decisions.